ANALISIS KEAMANAN LERENG DAN DAYA DUKUNG PONDASI UNTUK DAERAH BERLERENG CURAM DI TEGALALANG, GIANYAR-BALI - I Gusti Ngurah Putu Dharmayasa; Dewa Ayu Nyoman Ardi Utami (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2017)
ABSTRACT The rapid development of tourism in Bali demands the availability of tourism facilities such as hotels, villas, inns and restaurants that can improve services to tourists. Due to the difficulty of finding land to build hotels and villas as well as to get a natural atmosphere, many villas and hotels are built on steep slopes and even on the edge of a cliff. One of the many villas and hotels planned to be built on steep slopes is a villa in Dukuh, Tegalalang, Gianyar, Bali. Before the tourism facilities are built it is necessary to analyze the safety of the slope and the soil bearing capacity in the location of the villa so it can be planned the depth and the size of the foundation that meet the safety requirements. Slope safety analysis has been done using SLOPE/W 2007 program and with manual calculation using Bishop method. For this analysis is required some data ie SPT data, CPT data, soil shear angle (Ï•), soil cohesion value (c), soil density (Î³) and load on the building. The results of the analysis show that the location has a slope of 25 Â° - 33 Â° so that it is quite steep. The slope safety value (SF) obtained with the SLOPE / W is 1.00 in the location A-A and 1,431 in the B-B location, whereas the Bishop method is 0.91 in the location A-A and 1.10 in the location B-B, and it is quite vulnerable to the landslide. Analysis of foundation bearing capacity is planned with single bored pile with length of pile is 10 meters and using pile diameter 20 cm, 25 cm, 30 cm, 35 cm, 40 cm and 50 cm, is obtained the lowest allowable pile capacity based on data CPT and the highest allowable pile capacity based on laboratory data. Based on the structural analysis is obtained the maximum axial load (Pmax) on the foundation is 68456.67 kg and the pile diameter is 30 cm. The minimum axial load (Pmin) is 18085.26 kg and the pile diameter is 20 cm. Keywords: steep slope, Tegalalang, slope safety, bored pile